2020
DOI: 10.1049/iet-bmt.2019.0155
|View full text |Cite
|
Sign up to set email alerts
|

3D face mask presentation attack detection based on intrinsic image analysis

Abstract: Face presentation attacks have become a major threat to face recognition systems and many countermeasures have been proposed in the past decade. However, most of them are devoted to 2D face presentation attacks, rather than 3D face masks. Unlike the real face, the 3D face mask is usually made of resin materials and has a smooth surface, resulting in reflectance differences. So, we propose a novel detection method for 3D face mask presentation attack by modeling reflectance differences based on intrinsic image … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…However, head motions and rPPG signals are easily imitated in the replay attack, making such dynamic clues less reliable. Basing on the fact that replay attacks usually have abnormal reflection changes, Li et al [116] propose to capture such illumination changes using a 1D CNN with inputs of the intensity difference histograms from reflectance images.…”
Section: Hybrid (Handcraft + Deep Learning) Methodsmentioning
confidence: 99%
“…However, head motions and rPPG signals are easily imitated in the replay attack, making such dynamic clues less reliable. Basing on the fact that replay attacks usually have abnormal reflection changes, Li et al [116] propose to capture such illumination changes using a 1D CNN with inputs of the intensity difference histograms from reflectance images.…”
Section: Hybrid (Handcraft + Deep Learning) Methodsmentioning
confidence: 99%
“…In terms of vision applications, concepts of human material perception have been developed into image quality assessment [45] and video quality assessment [46]. For face anti-spoofing task, few works [17,18,47] consider discrepant surface reflectance properties of live or spoofing faces. However, only considering surface reflectance properties is not always reliable for material perception [1].…”
Section: Human and Machine Materials Perceptionmentioning
confidence: 99%
“…The proposed solution derives texture-dependent functionality from isolated wavelet processed images dependent on Local Binary Se-quence against Dataset 3D mask attack. Li et al [11] suggested an innovative 3D face mask attack detection approach based on visual refractive analysis. The face picture was first analyzed in the proposed approach using an inherent picture decomposition technique to measure the image reflectance.…”
Section: Related Workmentioning
confidence: 99%